Thyroid Imaging Reporting and Data System (TI-RADS) Stratification for Thyroid Incidentalomas in Iraqi Sample - Shaymaa Abdulqader (Kirkuk Journal of Medical Sciences, 2024)
Background: The detection of thyroid incidentalomas is on the rise due to high-resolution ultrasonography. Thisstudy aimed to evaluate the prevalence of thyroid incidentaloma in a sample of the Iraqi population through the use ofhigh-resolution ultrasound and to define the TI-RADS classification system.Method: This cross-sectional study was conducted at AL Kindy Teaching Hospital in Bagdad-Iraq. A total of 303 patientswere referred to the ultrasound unit for complaints other than neck pathology. A thyroid ultrasound examination wascarried out, and the American College of Radiology (ACR) thyroid imaging reporting and data system TI-RADS wasrecorded when an incidental thyroid nodule was found. Patients were grouped according to the thyroid ultrasound scaninto groups A: 102 participants with incident thyroid nodules; B: 201 participants without identified nodules.Results: Incidental thyroid nodules were detected in (33.66%) of the current sample, (20.8%) had solitary noduleswhile multiple nodules were detected in (12.9 %) of the individuals. Compared to those who did not show nodules,incidentaloma was identified in 49 (48%) of the older age group (46-60 years), P<0.001 and (20.59%) of those withenlarged thyroid gland, P<0.001 with no significant sex predilection. According to the internal texture of the nodules(27.45%) had echogenic texture, followed by hypoechoic t (22.55 %). Approximately one-third of incidentaloma wereTIRADS 4 nodules forming the majority (33.33%) followed by TIRAD 3 (30.39%).Conclusion: Ultrasound is a valuable test in detecting incidental thyroid nodules. prevalence of incidental thyroidnodules in Iraqi individuals is (33.7%), and the highest percentage of the detected nodules are classified as moderatelysuspicious according to the ACR TI-RADS.